Early tracheostomy in ventilated stroke patients: study protocol of the international multicentre randomized trial SETPOINT2 (Stroke-related Early Tracheostomy vs. Prolonged Orotracheal Intubation in Neurocritical care Trial 2): - Schönenberger, Silvia; Niesen, Wolf-Dirk; Fuhrer, Hannah; Bauza, Colleen; Klose, Christina; Kieser, Meinhard; Suarez, José I.; Seder, David B.; Bösel, Julian (International journal of stroke, 2016)
Tracheostomy is a common procedure in long-term ventilated critical care patients and frequently necessary in those with severe stroke. The optimal timing for tracheostomy is still unknown, and it is controversial whether early tracheostomy impacts upon functional outcome.
Gesehen am 22.05.2020